Coating formation, fracture mode and cavitation performance of Fe40Al deposited by cold gas spraying. (21st November 2014) - Cinca, N.; List, A.; Gärtner, F.; Guilemany, J. M.; Klassen, T.
Abstract : The present study investigates the coating formation by cold spraying Fe–40 at.-%Al intermetallics and evaluates their cavitation performance. Coating properties identify them as good candidates for application in many industrial environments. Despite their low ductility, after optimising the spraying parameters, dense layers were achieved. Fracture surfaces after bending tests indicate a combination of ductile and brittle failure, revealing some information on bonding features. The high microstructural homogeneity of these coatings, similar to that of bulk materials, is beneficial for their resistance to cavitation damage. The high strength of cold sprayed intermetallics makes them an interesting alternative to other materials and coating solutions.